Sliding Scale in the Management of Allergic Conjunctivitis: Doi:10.36351/pjo.v36i4.1055 - Jamil, Ahmad Zeeshan; Ali Bahoo, Muhammad Luqman; Kamal, Zahid; Rizwan, Muhammad; Ovais, Muhammad (Pakistan Journal of Ophthalmology, 2020)
Purpose: To verify the usability of the sliding scale in the management of allergic conjunctivitis. Study Design: Quasi-Experimental. Place and Duration of Study: District Headquarter Teaching Hospital/Sahiwal Medical College, Sahiwal, from January 2016 to December 2019. Methods: A sliding scale was developed and used to score the severity of the ocular allergy. Patients were instructed to use the sliding scale to adjust the treatment regimen and follow-up at regular intervals. At baseline and at third follow-up visit, sliding scale score and use of drug regimens were noted. At third follow-up visit patient’s satisfaction and disease control were documented. Results: There were 398 patients. Mean age of Patients was 29.45 ± 18.77 years. At baseline, 62.8% of patients were using topical steroids while at third follow-up visit only 5% of patients were using topical steroids. Mean interval of patients’ visit to the hospital was 8.53 ± 1.44 weeks. Nonparametric Mann Whitney test was used to calculate the difference in means of sliding scale scores at baseline (4.49 ± 2.39) and third follow-up visit (1.03 ± 1.68). Z score value was -16.917 and significance was 0.000.For patient’s satisfaction at third follow-up visit Chi-square value was 263.759 with significance value of 0.000. For disease control at third follow-up visit chi-square value was 223.123 with significance value of 0.000. Conclusion: Use of sliding scale in the management of allergic conjunctivitis was well accepted by the patients. It helped in disease control with minimal use of topical steroids and less frequent visits to the hospital. Key Words: Allergic Conjunctivitis, Steroids, Trantas dots.